Coenzyme Q10 Status as a Determinant of Muscular Strength in Two Independent Cohorts. - Alexandra Fischer; Simone Onur; Petra Niklowitz; Thomas Menke; Matthias Laudes; Gerald Rimbach; Frank Döring (PLoS ONE, 2016)
Aging is associated with sarcopenia, which is a loss of skeletal muscle mass and function. Coenzyme Q10 (CoQ10) is involved in several important functions that are related to bioenergetics and protection against oxidative damage; however, the role of CoQ10 as a determinant of muscular strength is not well documented. The aim of the present study was to evaluate the determinants of muscular strength by examining hand grip force in relation to CoQ10 status, gender, age and body mass index (BMI) in two independent cohorts (n = 334, n = 967). Furthermore, peak flow as a function of respiratory muscle force was assessed. Spearman's correlation revealed a significant positive association between CoQ10/cholesterol level and hand grip in the basic study population (p<0.01) as well as in the validation population (p<0.001). In the latter, we also found a negative correlation with the CoQ10 redox state (p<0.01), which represents a lower percentage of the reduced form of CoQ10 (ubiquinol) in subjects who exhibit a lower muscular strength. Furthermore, the age of the subjects showed a negative correlation with hand grip (p<0.001), whereas BMI was positively correlated with hand grip (p<0.01), although only in the normal weight subgroup (BMI <25 kg/m2). Analysis of the covariance (ANCOVA) with hand grip as the dependent variable revealed CoQ10/cholesterol as a determinant of muscular strength and gender as the strongest effector of hand grip. In conclusion, our data suggest that both a low CoQ10/cholesterol level and a low percentage of the reduced form of CoQ10 could be an indicator of an increased risk of sarcopenia in humans due to their negative associations to upper body muscle strength, peak flow and muscle mass.